The Subversion of Ageism And Sisterhood in Diana Wynne Jones’ Howl's Moving Castle - Januaristi, Khairiyah Eka; Novinda, Kushardiyanti; Jiwandono, Daud (POETIKA, 2025)
The aim of this study is to examine the subversion of ageism and female identity in Jones’ Howl Moving Castle through the lens of deconstruction and postmodern feminism. This novel challenges Young Adult Literature (YAL) conventions, where protagonists are typically young. On the contrary, Sophie Hatter is cursed by a witch into an older woman, but instead discovers agency, confidence, and self-worth. Collected data related to the contestation of ageist and patriarchal assumptions are then investigated carefully using Critical Discourse Analysis (CDA). The findings of this study suggest that the narrative demonstrates fluidity of identity, not strictly defined by age transformation and biological ties of sisterhood. Elements of fantasy employed in this novel function as more than a genre, allowing for fluid identity, which facilitates emotional support and mutual empowerment, rather than female rivalry. Through Sophie’s metamorphosis and the symbolism of the ever-moving castle, the fantasy setting operates as a critical space that redefines freedom, agency, and female solidarity beyond patriarchal and ageist constraints. Resisting age, gender, and identity stereotypes, this novel successfully expands the issues of representation in YAL. It establishes the possibility that fantasy, as a genre, is a powerful medium for critique and redefinition of age, identity, and sisterhood.